Effects of Muscle Fatigue, Creep, and Musculoskeletal Pain on Neuromuscular Responses to Unexpected Perturbation of the Trunk: A Systematic Review - Abboud, Jacques; Lardon, Arnaud; Boivin, Frédéric; Dugas, Claude; Descarreaux, Martin (Frontiers in Human Neuroscience, 2017)
Introduction Trunk neuromuscular responses have been shown to adapt under the influence of muscle fatigue, as well as spinal tissue creep or even with the presence of low back pain. Despite a large number of studies exploring how these external perturbations affect the spinal stability, characteristics of such adaptations remains unclear. Aim The purpose of this systematic review was to assess the quality of evidence of studies investigating trunk neuromuscular responses to unexpected trunk perturbation. More specifically, the targeted neuromuscular responses were trunk muscle activity reflex and trunk kinematics under the influence of muscle fatigue, spinal creep and musculoskeletal pain. Methods A research of the literature was conducted in Pubmed, Embase and Sport-Discus databases using terms related to trunk neuromuscular reflex responses, measured by electromyography (baseline activity, reflex latency, and reflex amplitude) and/or trunk kinematic, in context of unexpected external perturbation. Moreover, independent variables must be either trunk muscle fatigue or spinal tissue creep or low back pain. All included articles were scored for their electromyography methodology based on the “Surface Electromyography for the Non-Invasive Assessment of Muscles (SENIAM)” and the “International Society of Electrophysiology and Kinesiology (ISEK)” recommendations whereas overall quality of articles was scored using a specific quality checklist modified from the Quality Index. Meta-analysis was performed on reflex latency variable. Results A final set of 29 articles underwent quality assessments. The mean quality score was 79%. No effect of muscle fatigue on erector spinae reflex latency following an unexpected perturbation, nor any other distinctive effects was found for back muscle fatigue and reflex parameters. As for spinal tissue creep effects, no alteration was found for any of the trunk reflex variables. Finally, the meta-analysis revealed an increased erector spinae reflex latency in patients with chronic low back pain in comparison with healthy controls following an unexpected trunk perturbation. Conclusion The literature provides some evidence with regard to trunk adaptions in a context of spinal instability. However, most of the evidence was inconclusive due to a high methodological heterogeneity between the studies.